Dysregulation in IFN-γ signaling and response: the barricade to tumor immunotherapy - Han, Jiashu; Wu, Mengwei; Liu, Ziwen (Frontiers in Immunology, 2023)
Interferon-gamma (IFN-γ) has been identified as a crucial factor in determining the responsiveness to immunotherapy. Produced primarily by natural killer (NK) and T cells, IFN-γ promotes activation, maturation, proliferation, cytokine expression, and effector function in immune cells, while simultaneously inducing antigen presentation, growth arrest, and apoptosis in tumor cells. However, tumor cells can hijack the IFN-γ signaling pathway to mount IFN-γ resistance: rather than increasing antigenicity and succumbing to death, tumor cells acquire stemness characteristics and express immunosuppressive molecules to defend against antitumor immunity. In this review, we summarize the potential mechanisms of IFN-γ resistance occurring at two critical stages: disrupted signal transduction along the IFNG/IFNGR/JAK/STAT pathway, or preferential expression of specific interferon-stimulated genes (ISGs). Elucidating the molecular mechanisms through which tumor cells develop IFN-γ resistance help identify promising therapeutic targets to improve immunotherapy, with broad application value in conjugation with targeted, antibody or cellular therapies.